Efficacy of combination of fluoride varnish and cheese in white spot lesions remineralization evaluated using laser fluorescence - Wan Fauzi, Wan Nurfazliyana; Mohd. Azme, Zati Balqis; Sukmasari, Susi; Kusumawardani, Anisa; Zainol, Iswan Zuraidi (2015)
AIM AND PURPOSE: To investigate the effectiveness of combining the application of fluoride varnish with chewing cheese in white spot lesions remineralisation. MATERIALS AND METHOD:A researcher blinded quasi experimental study was conducted on 521 occlusal white spot lesions (OWSL) of 69 dental students with age between 20-21 years old who were randomly assigned into three different treatment groups; Fluoride varnish (FV), Cheese (C) and combination of Fluoride varnish and Cheese (FVC). The reduction of DIAGNOdent reading (DR) values represented OWSL remineralization. The DR at screening was compared with 2nd, 4th and 6th weeks follow–up. Repeated Measures Anova was used for data analysis. RESULTS: The mean (±SD) DR of FV at screening, 2nd, 4th and 6th week follow-up were, 13 (±5.40), 10(±7.53), 10 (±7.23) and 9 (±6.23); those of C were 13 (±5.15), 11 (±7.46), 11 (±6.96) and 10 (±7.04); and those of FVC were 14 (±5.56), 13 (±9.81), 12 (±8.57) and 11 (±7.31) respectively. All treatment groups showed reduction of DR, however the DR was increased in FV at 4th week follow-up. Levene’s Test of Equality of Error Variances showed significant of DR at 2nd and 6th week follow-up (p=0.00 and p=0.04) respectively whereas there were no significant of DR at screening and 4th week follow-up (p=0.39 and p=0.07) respectively. CONCLUSIONS: All 3 treatments had remineralisation effect on white spot lesions. With significant results at 2nd and 6th week, however the most effective group cannot be determined.